Maximum mouth opening measurement in relation to maximum bite force among children - Dalya Rafie Mohammed; Aseel Haidar MJ Al Haidar (University Library System, University of Pittsburgh, 2024)
Objective: This research aimed to study the relation between maximal bite force (MBF) and maximum mouth opening among 12-year-old school children. Methods: In this cross-sectional study, a total of 400 children aged 12 years (194 boys and 206 girls) were examined. The MBF for the right and left side, as well as the anterior region, were evaluated for all children. The MMO was measured using an electronic digital caliper. To analyze the data path analysis method was used. Results: Boys showed a higher MMO of 48.797 ± 6.500 than girls (46.710 ± 5.926 mm). The MMO increased with increasing MBF, with significant differences between females and males. Conclusion: The MMO was higher in boys than in girls. Gender plays a significant role in MBF strength.